Shahrastani’s Exposition of Judaism in al-Milal wa al-Nihal in the Light of Comparative Theology - Maulana, Abdullah Muslich Rizal; Untung, Syamsul Hadi; Nuriz, M. Adib Fuadi; Awaludin, Asep; Qorib, Khoffifa Assakhyyu (Ulumuna, 2023)
This article aimed to offer a closer comprehension concerning Judaism in the work of Abū al-Fath Muhammad ibn ’Abd al-Karīm ibn Ahmad al-Shahrastānī’s (d. 1153) work in the study of religions, al-Milal wa al-Nihal. Employing content and document analysis methods, this research goes over the framework of Comparative Theology, advancing further perspectives and considerations of Islamic-Jewish relations built within medieval Islamic literature. This research concluded that the employment of Comparative Theology as a framework led to an enhancement of reading the content of al-Milal wa al-Nihal¸ involving a novel procedure to develop the dialogue between Islam and other religions through the schema of ‘Commitment’ and ‘Openness.’ With a particular reference to the research question offered, this research was able to grasp a deeper yet broader cognition of the relevance of Comparative Theology as a cutting-edge perspective concerning the discussion of Sēp̄er Yəṣīrā, Tanakh, aséret ha-dvarím, and Joshua continued leadership in Judaism about Islam, which, as such, provided an extensive discussion of the study of Islam and Other Religions, particularly on Jews-Islam theological encounters.